Track of H.M. Sledge, "Murchison" from Dealy Island to Cape Fisher, May 9th [to] June 9th 1853 / Day & Son Lithr. to the Queen - Pim, Bedford (Hydrographic Office of the Admiralty, 1853)
Map includes illustration of the flag with Sir John Barrow's motto ‘HOPE ON HOPE EVER’ made by Lady Jane Franklin for Lieutenant Bedford Clapperton Tryvillion Pim (1826-86). Color;